Mr. Putin : operative in the Kremlin - Hill, Fiona, 1965-; Gaddy, Clifford G. (Brookings focus books., 2015)
"Who is Vladimir Putin? In Mr. Putin, Russia experts Fiona Hill and Clifford Gaddy argue that Russia's President, Vladimir Putin, is in fact a man of many and complex identities. Drawing on a range of sources, including their own personal encounters, they describe six that are most essential: the Statist, the History Man, the Survivalist, the Outsider, the Free Marketeer, and the Case Officer. Understanding Putin's multiple dimensions is crucial for policymakers trying to decide how best to deal with Russia."--Publisher's website